Post-traumatic digital flexion contracture (checkrein deformity) - Macklin Vadell, Alberto; Sperone, Enzo; Rofrano, Martín; Bigatti, Andrés; Iglesias, Matías; Torterola, Iván (Journal of the Foot & Ankle, 2021)
Objective: The aim of this study is to present a series of 8 patients, describing their clinical picture and assessing their treatment using plantar approach. Methods: We retrospectively assessed 8 patients, all of which had a history of trauma. The clinical characteristics of these cases and postoperative results were investigated. Results: Seven men and 1 woman with a mean age of 29 years were included. The follow-up period ranged from 6 to 28 months (mean 22 months). The deformity manifested from 5 to 24 months after the triggering injuries (mean 9.8 months). The hallux was the only digit affected in 1 patient, while the others presented with involvement of 1 or more small toes. There were no postoperative complications, and patients showed to be satisfied with functional outcomes. Conclusion: Post-traumatic digital flexion contracture is an infrequent disease of unknown etiology. Lengthening of the flexor hallucis longus using a plantar approach, whether at the level of the midfoot or the toe, represents an alternative with satisfactory outcomes. Level of Evidence IV; Therapeutic Study; Case Series.